Diagnosis and Treatment of Pneumocystis Carinii Pneumonia (PCP)/Pneumocystis Jirovecii Pneumonia in HIV patient: A Case Report - Agustina, Dewi Rizki; Efiyanti, Christy; Yunihastuti, Evy (UI Scholars Hub, 2017)
Pneumocystis carinii pneumonia (PCP) or pneumocystis jirovecii pneumonia is an opportunistic infection that can occur in immunocompromised patients. In patients with HIV, PCP is the most common opportunistic infection especially in patients with CD4 cell counts less than 200 cell /ul. To diagnose a PCP is very difficult because symptoms, blood tests, and thoracic radiography are not pathognomonic for PCP. However, untreated PCP is almost always fatal. Trimethroprimsulfamethoxazole (TMX-SMX) orally or intravenously for 21 days is the drug of choice for managing PCP with or without HIV. This article discusses a case with patients with symptoms of dyspneu, unproductive cough, diagnosed with PCP and finally improvement with TMX-SMX therapy